Enhanced Intestinal Absorption of Insulin by Capryol 90, a Novel Absorption Enhancer in Rats: Implications in Oral Insulin Delivery - Hiroki Ukai; Kazuki Iwasa; Takamasa Deguchi; Masaki Morishita; Hidemasa Katsumi; Akira Yamamoto (Pharmaceutics, 2020)
Labrasol® is a self-emulsifying excipient that contains saturated polyglycolysed C6–C14 glycerides and this additive is known to improve the intestinal absorption of poorly absorbed drugs after oral administration. However, the effects of formulations similar to Labrasol® on the intestinal absorption of poorly absorbed drugs have not been characterized. In this study, we used insulin as a model peptide drug and examined the absorption-enhancing effects of Labrasol® and its related formulations for insulin absorption in rats. The co-administration of Labrasol-related formulations with insulin reduced the blood glucose levels. Among these formulations, Capryol 90 was the most effective additive. Notably, the effect of Capryol 90 was greater at pH 3.0 than at pH 7.0. Additionally, almost no mucosal damage was observed in the presence of these formulations, as these formulations did not affect the activity of lactate dehydrogenase (LDH) and the amount of protein released from the small intestine. In mechanistic studies, Capryol 90 improved the stability of insulin and suppressed the association with insulin under acidic conditions. The loosening of the tight junctions (TJs) could be the underlying mechanism by which Capryol 90 improved intestinal insulin absorption via a paracellular route. These findings suggest that Capryol 90 is an effective absorption enhancer for improving the intestinal absorption of insulin, without inducing serious damage to the intestinal epithelium.